Octreotide in the treatment of neonatal postoperative chylothorax : report of three cases and literature review - Pinto, João Moreira (2011)
Chylothorax is a well-recognized omplication after neonatal cardiothoracic surgery. Management strategies include cessation of enteral feedings, repeated aspiration, chest drainage, and total parenteral nutrition. Somatostatin and its analogue, octreotide, have been used with promising results. The authors present three cases of neonatal postoperative chylothorax in which ctreotide was used. After literature review, we can say that octreotide is relatively safe, and may reduce clinical course and complications associated with neonatal postoperative chylothorax. One should be aware of possible association between octreotide and necrotizing enterocolitis. Prospective controlled trials supporting octreotide use are lacking.